2016
DOI: 10.1039/c6cc00847j
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-coated open cell polyurethane foams as an inexpensive, flexible yet robust catalyst support: a proof of concept

Abstract: Commercially available polyurethane open cell foams are readily coated with mussel-inspired polydopamine. The polydopamine film allows robust immobilisation of TiO2 nanoparticles at the surface of the three-dimensional material. The resulting catalyst is efficient for the photo-degradation of an azo dye, reusable and highly resistant to mechanical stress. A novel type of robust structured catalytic support, easily accessible via an inexpensive and green process, is thus described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…2.07 6 0.12 lmol.g 21 ). Scanning electron microscopy (SEM) images of PDA-NaIO 4 @OCPUF and NaBH 4 @PDA-NaIO 4 @OC-PUF show aggregates of PDA, having micrometer size, randomly distributed on the whole surface of each foam, as previously reported (Figure 2) [24]. These aggregates appear comprised of several layers on both types of foams.…”
Section: Preparation and Characterization Of Nabh 4 @Pda@ocpufsupporting
confidence: 79%
See 2 more Smart Citations
“…2.07 6 0.12 lmol.g 21 ). Scanning electron microscopy (SEM) images of PDA-NaIO 4 @OCPUF and NaBH 4 @PDA-NaIO 4 @OC-PUF show aggregates of PDA, having micrometer size, randomly distributed on the whole surface of each foam, as previously reported (Figure 2) [24]. These aggregates appear comprised of several layers on both types of foams.…”
Section: Preparation and Characterization Of Nabh 4 @Pda@ocpufsupporting
confidence: 79%
“…o ‐quinone) are disseminated all over the surface, underlying the reductive power of PDA . Recently, PDA was shown to play the role of redox mediator , thus allowing the use of soft structured materials such as PDA@OCPUF for the efficient reduction of MB in the presence of a large excess of NaBH 4 . Although being thermodynamically favorable, the reduction of MB with NaBH 4 is indeed kinetically restricted in the absence of a catalyst .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That should help dispersing the metal precursors through specific bonding, while avoiding direct detrimental strong interactions with the surface groups on the bare alumina support. Very recently, it was shown that Pdop coating of polyurethane improved its adherence capacity to deposit a catalytic phase (TiO 2 ) …”
Section: Introductionmentioning
confidence: 99%
“…Inspired both by the adhesive and reducing properties of polydopamine (PDA), as well as our previous works, [28][29][30] the polyurethane open-cell foams were pre-functionalized with a polydopamine layer (OCPUF@PDA) to offer sufficient stability to a cobalt active phase. The choice of cobalt as the active phase was driven by the necessity to keep the costs as low as possible and to use earth-abundant metals.…”
Section: Nabh 4 + 2h 2 O ! Nabo 2 + 4h 2 : ð1þmentioning
confidence: 99%